A discriminação no discurso: a categorização da mulher sob o enfoque da linguística sistêmico-funcional - Santos, Claudia Moreira dos (2011)
It isn t neither uncommon nor surprising when we hear on the streets male drivers crying to a female driver: Go to the kitchen! or Cooking is what you should be doing! as if women who dare drive had invaded a man s territory. I have always felt puzzled by such attitude towards women s chores against men s duties. If we picture the world as a vast collection of things and people one could understand such rights. Therefore, getting acquainted with Fowler s ideas on women s categorization and groupings made me decide to go deep inside it. Human communication, according to Fowler, involves belief systems, labeling arrangements and degrees of discrimination, which all together represent the world according to the needs of the societies where communication takes place. As we proceed with categorization of people, we go on assigning persons specific attributes and associating them with strongly predictable behaviors in a way that the categories end up turning into stereotypes. According to Fowler, categorization is a discursive basis for discrimination. He is one of the creators of Critical Linguistics which says that analysis made with appropriate linguistic tools and related to relevant social and historical contexts may reveal the ideology hidden under the surface of ordinary discourse and display it for inspection. Because there are also images which we picked up from the newspaper and included in this study, we refer to Macken-Horarik (2004) to account for the complementary contribution of image (artwork) and verbiage (text panel) to the meaning-making process. The objective of this study is to compare the categorization of women and men on the first page of Folha de S. Paulo newspaper, under the light of Critical Linguistics (Fowler 1991), with the support of Systemic Functional Linguistics (Halliday, 1985; 1994). For this purpose, the study shall answer the following questions: (a) How often are women or men cited on the first page of Folha de S. Paulo newspaper? (b) What type of activities do women and men cited on these pages are engaged in? (c) Which lexico-grammatical choices does the ideology behind the image of woman and man reveal? The corpus of this research is composed by the first pages of the thirty editions of Folha de S. Paulo in April 2010. From Systemic Functional Linguistics, I consider the TGR (Theory of Genres and Register), proposed by Eggins and Martin (1997), as well as more recent contributions that such theory has received, such as Martin´s Appraisal Theory (2000) and the concepts of Thompson and Thetela´s enacted and projected roles (1995), and some other rhetoric features as well as the so-called dog whistle politics (COFFIN & O'HALLORAN, 2006) or smuggling of information (LUCHJENBROERS; ALDRIDGE, 2007)